2010
DOI: 10.1016/j.jmb.2010.01.024
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal Lysine of Ogg2 DNA Glycosylases is a Major Molecular Determinant for Guanine/8-Oxoguanine Distinction

Abstract: 7,8-dihydro-8-oxoguanine (8-oxoG) is a major oxidative lesion found in DNA. The 8-oxoguanine DNA glycosylases (Ogg) responsible for the removal of 8-oxoG are divided into three families: Ogg1, Ogg2 and AGOG. Since Ogg2 members are devoid of the recognition loop used by Ogg1 to discriminate between 8-oxoG and guanine it was unclear until recently how Ogg2 enzymes recognize the oxidized base. We present here the first crystallographic structure of an Ogg2 member, Methanocaldococcus janischii Ogg, in complex with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
(77 reference statements)
1
21
0
Order By: Relevance
“…Despite very low sequence identity with hOGG1, structures of OGG2 from Methanocaldococcus janischii (MjOGG) and Sulfolobus solfataricus (SsOGG) confirmed that these enzymes adopt the HhH fold and contain the catalytic lysine and aspartate residues present in OGG1, but lack the N-terminal β-sheet domain [65] (Figure 4D). The structure of MjOGG in complex with 8oxoG-DNA illustrated that the OGG2 family of enzymes utilize a distinct mechanism for identification of 8oxoG in the active site, in which the C-terminal carboxylate group of Lys207, as opposed to the Gly42 backbone carbonyl interaction in hOGG1, interacts with the N7 of 8oxoG [84] (Figure 4E). Deletion of the three C-terminal residues abolished 8oxoG excision activity in MgOGG, but did not significantly affect enzyme integrity since the truncation only slightly diminished lyase activity [65].…”
Section: Oxidative Damagementioning
confidence: 99%
“…Despite very low sequence identity with hOGG1, structures of OGG2 from Methanocaldococcus janischii (MjOGG) and Sulfolobus solfataricus (SsOGG) confirmed that these enzymes adopt the HhH fold and contain the catalytic lysine and aspartate residues present in OGG1, but lack the N-terminal β-sheet domain [65] (Figure 4D). The structure of MjOGG in complex with 8oxoG-DNA illustrated that the OGG2 family of enzymes utilize a distinct mechanism for identification of 8oxoG in the active site, in which the C-terminal carboxylate group of Lys207, as opposed to the Gly42 backbone carbonyl interaction in hOGG1, interacts with the N7 of 8oxoG [84] (Figure 4E). Deletion of the three C-terminal residues abolished 8oxoG excision activity in MgOGG, but did not significantly affect enzyme integrity since the truncation only slightly diminished lyase activity [65].…”
Section: Oxidative Damagementioning
confidence: 99%
“…At Lys204, the ORF of TVG_RS00315 also possessed a C-terminal lysine (Lys207 in MjaOgg and Lys207 in SsoOgg) that discriminates between G and GO. In MjaOgg, Phe85 is wedged between the estranged cytosine and its 5′-neighbor, His133 and Trp198 sandwich the aberrant GO, and Arg84 interacts with the estranged cytosine [ 13 ]; all of these crucial residues were conserved in the putative TvoOgg, TVG_RS00315 ( Figure 1 ). These results strongly suggested that the ORF of TVG_RS00315, TvoOgg, is a homolog of Ogg2.…”
Section: Resultsmentioning
confidence: 99%
“…Ogg2 lacks amino acid residues Asn149, Arg154, and Tyr203 when compared to hOGG1, providing an explanation for Ogg2's reduced specificity, relative to Ogg1, for the base positioned opposite the lesion. The C-terminal lysine of Ogg2 may play a key role in discriminating between G and GO [ 13 ]. This prediction was confirmed by measuring the glycosylase/lyase activity of a deletion mutant of MjaOgg lacking the three amino acids at the C-terminal and subsequent cocrystallization of MjaOgg with DNA containing GO sequences [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hOGG1 enzyme (a functional analog of Fpg/MutM in E. coli) preferentially recognizes 8-oxoG:C, while hOGG2 has similar functionality yet with less specificity for the opposite base. [84][85][86] The bacterial MutT enzyme (preserved in humans as the hMTH1 enzyme) recognizes 8-oxo-dGTP and produces monophosphates that cannot be incorporated during replication. 80 If 8-oxoG damage evades repair and is replicated with an A, MutY (human analog hMYH) can identify the 8-oxoG:A mispair and remove the A base.…”
Section: A 8-oxog Damagementioning
confidence: 99%